Reasoning to Transform: Philosophy and Critical Thinking in Higher Education - Cambronero Alpízar, José Rodolfo (2025)
This article seeks to contribute to the discussion on the role of higher education, and philosophy in particular, in the development of critical thinking among university students. This through a critical review of the opportunities offered by this discipline, taking advantage of processes of reflection, dialogue, and argumentation. It draws on contributions from philosophers and educators such as John Dewey, Paulo Freire, Boaventura de Sousa, Plato, Kant, Adela Cortina, Jürgen Habermas, and Cristóbal Orrego, among others, to show that philosophy allows us to question beliefs, analyze arguments, recognize fallacies, and assist in ethical decision-making. It also critiques the increasing technological development of education and proposes a critical pedagogy that considers reflection from the global south and strengthens democracy and active citizenship aiming toward genuine social transformation.